Análisis de la planta turística, oferta alimentación en el cantón LA MANÁ. - Chancusig Viracocha, Katherine Paola (2020)
The purpose of this project was to analyze the tourist plant, food supply in La Maná canton, in order to have updated information, first thing that was done is a bibliographic review in books and documents to obtain geographical, environmental, socio-cultural and tourist diagnosis , showing that the most part of the people are engaged to livestock, agriculture and panela productio, but a small part of them are involved to tourist activities due to ignorance or low support from local authorities, in addition to know the tourist plant was based on the cadastre from Ministry of Tourism 2019 year, where 34 food and beverage establishments are registered and through field trips it was possible to verify that the cadastre is outdated, because 17 establishments are closed and 17 in operation. Also for the inventory, technical sheets were filled out with the establishments owners help, having a total of 66 food and beverage establishments that are classified into 48 restaurants, four bars, four discos, four coffee shops, four food places and two fountains of soda, later the information was analyzed resulting in 25 establishments between tourist and non-tourist able to receive visitors, finally the tourist catalog was designed using Lunacy program that allowed to choose font, size and appropriate color to attract the reader attention, also at the catalog are only food and beverages establishments that meet the parameters to offer good service. With obtained results, it was possible to determine positive and negative aspects such as tourist increasing and the lack of follow-up to the establishments by regulatory institutions.